ANALYTICAL ESTIMATION OF THE THERMAL STABILITY OF HTS MAGNETS DURING SUDDEN DISCHARGE - Takanobu Mato; So Noguchi (Journal of Energy Technology, 2025)
Since the advent of 2nd-generation high-temperature superconducting (HTS) tapes, which show great features on critical temperature, critical current density, and critical magnetic field, many researchers have been trying to generate ultra-high magnetic fields using HTS coils. One more promising technology is a no-insulation (NI) winding technique. This technique suppresses the possibility of thermal runaway and burning-out of HTS coils drastically. The interest in compact nuclear fusion magnets wound with HTS conductors has been increasing rapidly during the last five years. The simulation of such magnets larger than MRI/NMR HTS magnets takes an unfeasibly long time. Therefore, we present a simple expression of the coil temperature rise under a simple assumption derived from the simple coil model, to investigate the stability of large-scale magnets. The method’s advantages are simplicity, versatility, and nearly no computation, enabling a time reduction in the first-cut design.